Pengaruh Pengungkapan Sustainability Report Terhadap Kinerja Keuangan Pada Perusahaan Makanan Dan Minuman Yang Terdaftar Di Bursa Efek Indonesia - Hamzah, Hajrah; Oktaviyah, Nurafni; Reskiyawati, Siti Nur; Hidayatullah, Andi Muh. Syukur (JEKPEND: Jurnal Ekonomi dan Pendidikan, 2025)
The purpose of this study is to investigate how the keuangan kinerja of companies that manufacture food and beverages and are listed on the Indonesian Stock Exchange (BEI) is affected when economic, environmental, and social factors are taken into consideration in a long-term report. This analysis highlights both the individual and the interconnected effects of the many components. While Return on Assets (ROA) is used as a dependent variable to assess financial performance, Indeks Pengungkapan Laporan Keberlanjutan (SRDI) is used as an independent variable to determine the level of pengungkapan keberlanjutan. Purposeful sampling is used to choose 13 businesses, covering the years 2021–2023. The documentation process is used to gather data, and analysis is done using the koefisien determinasi (R2), berganda line regression, uji t, uji F, and uji asumsi klasik. The findings show that financial performance is significantly and favorably impacted by disclosures about economic and environmental performance taken separately. Furthermore, when the three sustainability dimensions are tested simultaneously, the findings reveal a significant collective impact on financial outcomes, accounting for 65.5% of the variation in ROA. These findings suggest that sustainability disclosure serves as an effective strategy to enhance a company's financial performance while reinforcing accountability toward stakeholders.